Additive Manufacturing of Metals - Gibbons, Gregory John (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is an exciting collection of research articles that offer a unique view into the fast developing field of metal additive manufacturing, providing insights into this advanced manufacturing technology. The articles span recent advances in metal AM technologies, and their application to a wide range of metals, exploring how the processing parameters offer unique material properties. This book encapsulates the state of the art in this rapidly evolving field of technology and will be a valuable resource for researchers in the field, from Ph.D. students to professors, and through to industrial end users.